A study of special education teachers’ knowledge, perception, and self-efficacy in implementing sexual health education programs for youth with special needs - Sobberi, Sobberinissa; Roslan, Samsilah; Mohamad, Zulkifli; Zaremohzzabieh, Zeinab; Kamarudin, Kamariah (Human Resource Management Academic Research Society, 2022)
Special education teachers are seen as valuable collaborators in delivering controversial or sensitive topics to youth with special needs. Thus, the primary goal of this study is to determine the association between the teachers' perceptions, self-efficacy, and knowledge about sexual health education programs for youth with special needs. We conduct a cross-sectional study and recruit 96 special education teachers from the Melaka Tengah district. Simple random sampling techniques were used in the study, and data were obtained using a questionnaire. The findings show that the teachers have a high level of self-efficacy, a moderate level of perception, and a moderate level of knowledge regarding sexual health education for youth with special needs. The findings demonstrated a high association (r=.487, p=.001) between teachers' perceptions and their self-efficacy to implement a sexual health education component for special needs youth. Teachers' knowledge and self-efficacy in implementing a sexual health education component for special needs youth also had a significant association (r=.619, p=.001). Going forward, future opportunities for improving the quality of sexual health education for youth with special needs have discoursed. The results of this study suggest that the teachers’ knowledge, perception, and self-efficacy are fundamental domains for the proper implementation, as well as sustainability, of sexual health education, especially for youth with special needs.